2020
DOI: 10.1155/2020/9349762
|View full text |Cite
|
Sign up to set email alerts
|

Heme Oxygenase-1-Mediated Autophagy Protects against Oxidative Damage in Rat Nucleus Pulposus-Derived Mesenchymal Stem Cells

Abstract: Although endogenous nucleus pulposus-derived mesenchymal stem cell- (NPMSC-) based regenerative medicine has provided promising repair strategy for intervertebral disc (IVD) degeneration, the hostile microenvironments in IVD, including oxidative stress, can negatively affect the survival and function of the NPMSCs and severely hinder the endogenous repair process. Therefore, it is of great importance to reveal the mechanisms of the endogenous repair failure caused by the adverse microenvironments in IVD. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…1456 authors, 352 organizations, and 30 countries contributed to this field. Table 2 showed the top author with the most publications was Wang K ( n = 17) from Tongji Medical College ( Yin et al, 2021 ), the second was Shao ZW ( n = 16) from Tongji Medical College ( Chen S. et al, 2020 ), followed by Wang XY ( n = 15) from The Second Affiliated Hospital of Wenzhou Medical University ( Hu S. et al, 2021 ), Yang C ( n = 12) from Tongji Medical College ( Song et al, 2021 ), Zhang Y ( n = 12) from Third Military Medical University ( Xu et al, 2021 ). Of the 352 organizations, Huazhong University of Science Technology, Shanghai Jiao Tong University, Wenzhou Medical University, Zhejiang University, and Sun Yat Sen University had contributed 31, 21, 20, 15, and 12 publications, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…1456 authors, 352 organizations, and 30 countries contributed to this field. Table 2 showed the top author with the most publications was Wang K ( n = 17) from Tongji Medical College ( Yin et al, 2021 ), the second was Shao ZW ( n = 16) from Tongji Medical College ( Chen S. et al, 2020 ), followed by Wang XY ( n = 15) from The Second Affiliated Hospital of Wenzhou Medical University ( Hu S. et al, 2021 ), Yang C ( n = 12) from Tongji Medical College ( Song et al, 2021 ), Zhang Y ( n = 12) from Third Military Medical University ( Xu et al, 2021 ). Of the 352 organizations, Huazhong University of Science Technology, Shanghai Jiao Tong University, Wenzhou Medical University, Zhejiang University, and Sun Yat Sen University had contributed 31, 21, 20, 15, and 12 publications, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that autophagy played a protective role against the oxidative stress in degenerative NPCs [ 24 , 30 , 32 ]. In this research, a significantly different autophagy score between NPC/MSC samples and NPC samples was observed ( Figure 6(a) ).…”
Section: Resultsmentioning
confidence: 99%
“…The dysregulation of autophagy has been proved to associate with the development of several human diseases, including the IDD [ 21 , 23 ]. Previous studies have shown that the oxidative stress could be relieved by activating the autophagy in degenerative NPCs, thereby reducing the apoptosis and degradation of extracellular matrix [ 22 , 24 , 25 ]. Nevertheless, to our knowledge, few articles focus on the effects of MSCs on the alleviation of oxidative stress via regulating the autophagy in IDD.…”
Section: Introductionmentioning
confidence: 99%
“…OS inhibits cell viability, induces apoptosis, and finally promotes IDD (14). To evaluate the effects of OS induced by H 2 O 2 in human NP cells, we examined the viability and apoptosis of NP cells that had been treated with several H 2 O 2 concentrations using CCK-8 assays and a flow cytometry analysis.…”
Section: High Concentrations Of H 2 O 2 Inhibit Viability and Promote...mentioning
confidence: 99%